The effect of coconut dust addtion on the properties of green sand and investment casting moulds - S. Alyami, Saad Rabia (2010)
The purpose of this work is to investigate the effect of natural fiber produced from coconut shell on the mechanical properties of investment casting and green sand casting moulds. MOR, Strength, and permeability of the moulds are the subjects of evaluation in this work. The MOR test analyzes 3 systems: green undewaxed, green undewaxed and fired. The permeability test for the investment casting analyze 2 systems: green dewaxed and fired. Aluminosilicate and colloidal silicate are used to build the mould. The dewaxing temperature is 250 C° and firing temperature is 800 C°. The results for investment casting show that the green dewaxing system has the highest MOR values compared with the undewaxed and fired systems. Moreover, the fired system has the lowest MOR values among the 3 systems. Moreover, from the permeability test it was shown that the fired system has higher permeability values than the green dewaxed system. For green sand molding, with the percentage increase of the fiber, the strength and permeability tests showed that the permeability increased, but the strength decreased.